Thermal-mechanical responses of steel portal frame under varying fire scenes with diverse protective measures - Zhang, GuangPing; Zhang, ZhaoBo; Ma, HongYuan; Liu, HaiYang; Dong, ChangHong (Archives of Civil Engineering, 2026)
This study investigates the thermal-mechanical responses of steel portal frame without fire pro-tection and with different fire protection strategies across three fire scenes. Temperature fields and heating curves were derived for the steel portal frame in three fire scenes using FDS simulations. Abaqus was employed to perform thermal-mechanical coupling simulations on the steel portal frame under eight conditions, both unprotected and protected with two types of fire protection. A comprehensive comparison and analysis of the simulation results yielded the following key conclusions: in all three fire scenes, the absence of fire protection and the implementation of two different fire protection measures lead to distinct failure modes in the steel portal frame, yet the lateral displacement response patterns remain consistent. Although fire protection strategies can delay the onset of displacement responses in the steel portal frame during fires, their effectiveness in reducing these responses is limited. Furthermore, fire-resistant boards alter the heat transfer path within the steel portal frame, increasing the temperature differential across the component sections and subsequently amplifying bending deformation. The findings provide valuable in-sights that enhance fire safety design for steel portal frame under diverse conditions.